Japan remodeled : how government and industry are reforming Japanese capitalism - Vogel, Steven Kent (Ithaca : Cornell University Press, 2006)
"As the Japanese economy languished in the 1990s, Japanese government officials, business executives, and opinion leaders concluded that their economic model had gone terribly wrong. As government officials and industry leaders scrutinized their options, they selected reforms to modify or reinforce preexisting institutions rather than to abandon them. In Japan Remodeled, Steven K. Vogel explains the nature and extent of these reforms and why there are enacted." "Vogel demonstrates how government and industry have devised innovative solutions. The cumulative result of many small adjustments is, he argues, an emerging Japan that has a substantially redesigned economic model characterized by more selectivity in business partnerships, more differentiation across sectors and companies, and more openness to foreign players."--BOOK JACKET.
The Japanese model and institutional change -- The crisis of Japanese capitalism -- Policy reform Japanese style -- The varieties of reform -- Corporate restructuring Japanese style -- The varieties of restructuring -- Japan's new model.
Bibliografija: str. [225]-238 i kazalo.
Keywords: Japan -- ekonomska politika- 1989-. -- kapitalizam -- industrijska politika